Fonemy ś i ź w procesie różnicowania sztokawskiego obszaru językowego - Brom, Przemysław (Slavia Centralis, 2020)
The phonemes ś and ź in the process of differentiation in the Štokavian language areaIn the area of the Štokavian dialect there have been processes aiming at diversifying particular language standards. These activities have gathered pace ever since the South-Slavic national community disintegrated. The Montenegrin area is characterized by the occurrence of developed forms of the phonological process of iotization – including the Jekavian. The products of that process – the phonemes ś and ź – existed in all Montenegrin dialects to a significant degree. Nowadays it is possible to classify them as important elements of the norm of the Montenegrin language because of their frequent occurrence in the contemporary language standard.
Keywords: language; standard; Montenegro; phonemes